Evaluasi Penyaluran Pupuk Bersubsidi Di Kelurahan Ranowangko Kecamatan Tondano Timur Kabupaten Minahasa - Walangare, Miranda Evryl; Waney, Nordy Fritsgerald Lucky; Montolalu, Maya Hendrietta (Sam Ratulangi University, 2024)
This research aims to analyze the effectiveness and evaluate the distribution of subsidized fertilizer in Ranowangko Village, East Tondano District, Minahasa Regency based on the